Visual perception and visual cognition in healthy and pathological ageing - Mark W. Greenlee; Allison B. Sekuler (Frontiers Media SA, 2021)
Our understanding of visual perception and visual cognition has advanced considerably over the last decades. The effects of ageing on visual perception and visual cognition are less well understood. This Research Topic features state-of-the-art approaches to determining the effects of ageing on visual perception, visual attention, visual memory and visually guided behaviour. Studies using methods that incorporate psychophysics, eye movements, electrophysiology, structural and functional neuroimaging, as well as computational modelling are included. In addition to the focus on how ageing effects normal vision, the topic also includes studies on the effects of pathological ageing in the retina (e.g., age-related macular degeneration) and the brain (e.g., neurodegenerative disorders) on vision and visual cognition.